ANALISIS TIMBUNAN RINGAN MORTAR BUSA MENGGUNAKAN MESIN KONVERSI ENERGI PADA PROYEK FLY OVER - BILHAN GAMALIEL (CV KULTURA DIGITAL MEDIA, 2023)
The relatively high population growth rate as a result of the development in South Tangerang City has caused traffic jams during rush hour at the Gaplek intersection. This congestion can be minimized by constructing a Martadinata flyover without disturbing the existing transportation movements. Heap construction is often faced with several problems, including stability and reduction problems due to the weight of the pile load, due to vehicle traffic loads, and due to being above soft soil layers. This study aims to obtain the magnitude of the carrying capacity of the subgrade under light weight foam mortar, to obtain the amount of stability and reduction of light weight foam mortar to soft soil behavior. Comparative research to get a comparison between manual calculation and finite element calculation method plaxis 8.2 software. The results of the bearing capacity of the soil under lightweight foam mortar at a soil depth of 1.5 meters and 10 meters, the soil bearing capacity is 366,481 kN/m2 and 376,295 kN/m2. The stability results of the lightweight foam mortar pile above the soft soil layer due to the weight of the pile load of 3.52 and 12.53 due to vehicle traffic loads of 3.05 and 9.54 have met the minimum safety factor requirements for road class 1 of 1.4. The results of the reduction of light weight foam mortar are above the soft soil layer due to the weight of the embankment load of 11.91 mm year and 12.61 mm/year, due to vehicle traffic loads of 15.25 mm/year and 20.06 mm/year. meet the criteria for road embankment reduction of 20mm/year. So it can be concluded that the foam mortar stockpile at the Martadinata Pamulang Tengerang Selatan flyover has met the requirements in the technical planning guidelines for lightweight foam mortar pile on soft soil.